Landasan Filosofi dan Prinsip Pendidikan Teknologi & Kejuruan (PTK) menggunakan Metode Systematic Literature Review - Enjang Suhaedin; Nizwardi Jalinus; Rijal Abdullah (Journal on Education, 2023)
The current implementation of Vocational Technology Education (PTK) in Indonesia refers to Law no. 20 of 2003 concerning the National Education System. In its implementation, PTK adopts the principles of Vocational Education developed by Charles Prosser, known as the 16 PTK philosophies. This research is a literature study which aims to identify the philosophical foundations and principles of Technological and Vocational Education (PTK), using a qualitative descriptive approach to the scientific articles studied. The research method used is Systematic Literature Review (SLR) with the steps, namely (a) Developing a Research Question (RQ), (b) Searching for relevant literature, (c) Carrying out a review, (d) Analysis of findings. Philosophy as an attempt to describe the most basic and true nature of reality. In the context of Vocational Education in Indonesia, the basis of this philosophy refers to Prosser's theory which is embedded in a competency-based curriculum which focuses on mastering competencies relevant to the industrial world.